2013
DOI: 10.1120/jacmp.v14i4.4152
|View full text |Cite
|
Sign up to set email alerts
|

Free‐breathing conformal irradiation of pancreatic cancer

Abstract: The purpose of this study was to assess treatment margins in free‐breathing irradiation of pancreatic cancer after bone alignment, and evaluate their impact on conformal radiotherapy. Fifteen patients with adenocarcinoma of the head of the pancreas underwent implantation of single fiducial marker. Intrafraction uncertainties were assessed on simulation four‐dimensional computed tomography (4D CT) by calculating maximal intrafraction fiducial excursion (MIFE). In the first ten patients, after bony alignment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Markers implanted either in the tumor itself or nearby are often used as the internal surrogate with which to localize the tumor position. (13,14) Although van der Horst et al (13) stated that small changes in the pair distance of implanted markers over the course of treatment may be attributed to tissue deformation rather than to marker migration, we have previously experienced large marker migration. (This case was not a participating patient in the present study.)…”
Section: Lrmentioning
confidence: 87%
See 3 more Smart Citations
“…Markers implanted either in the tumor itself or nearby are often used as the internal surrogate with which to localize the tumor position. (13,14) Although van der Horst et al (13) stated that small changes in the pair distance of implanted markers over the course of treatment may be attributed to tissue deformation rather than to marker migration, we have previously experienced large marker migration. (This case was not a participating patient in the present study.)…”
Section: Lrmentioning
confidence: 87%
“…Several investigators have examined interfraction positional variation of the pancreas using a variety of methods; (12)(13)(14)19) however, most examinations were performed under free breathing. van der Horst et al (13) demonstrated large interfractional pancreatic position variation of > 10 mm using fiducial markers visible on daily CBCT scans.…”
Section: Lrmentioning
confidence: 99%
See 2 more Smart Citations
“…Solla et al present that the potential target underdosage may occur due to respiration and small PTV margin [27]. Several studies have shown a survival advantage for higher dose levels [2833].…”
Section: Discussionmentioning
confidence: 99%